2016
DOI: 10.1371/journal.pone.0165607
|View full text |Cite
|
Sign up to set email alerts
|

Increased Lytic Efficiency of Bovine Macrophages Trained with Killed Mycobacteria

Abstract: Innate immunity is evolutionarily conserved in multicellular organisms and was considered to lack memory until very recently. One of its more characteristic mechanisms is phagocytosis, the ability of cells to engulf, process and eventually destroy any injuring agent. We report the results of an ex vivo experiment in bovine macrophages in which improved clearance of Mycobacterium bovis (M. bovis) was induced by pre-exposure to a heat killed M. bovis preparation. The effects were independent of humoral and cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…bovis specific antigenic stimulation after vaccination is generally accepted to play an important role in the protective mechanism against BTB, emphasizing the role of cell-mediated immunity. This role was confirmed in an ‘ex vivo’ experiment carried out by Juste et al [ 19 ] which determined that bovine macrophages trained with the heat-killed M . bovis vaccine through intramuscular injection exhibited an increased lytic capacity, which was furthermore proposed as an underlying mechanism of vaccine protection.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…bovis specific antigenic stimulation after vaccination is generally accepted to play an important role in the protective mechanism against BTB, emphasizing the role of cell-mediated immunity. This role was confirmed in an ‘ex vivo’ experiment carried out by Juste et al [ 19 ] which determined that bovine macrophages trained with the heat-killed M . bovis vaccine through intramuscular injection exhibited an increased lytic capacity, which was furthermore proposed as an underlying mechanism of vaccine protection.…”
Section: Discussionmentioning
confidence: 69%
“…avium ; 1000 IU/ml) and PPD-F (purified protein derivative of M . fortuitum ; 28.5 μg/ml, ARC-Onderstepoort Veterinary Institute) [ 19 ]. One aliquot of whole blood was left unstimulated to serve as a negative control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NO production of trained monocytes may lead to increased killing capacity upon phagocytosis [26]. Indeed, a study in bovine monocyte-derived macrophages showed that increased bacterial killing capacity could be induced by macrophage training upon stimulation with heat-killed Mycobacteria bovis in vivo [27]. In that study, this was referred to as innate immune training.…”
Section: Discussionmentioning
confidence: 99%
“…TI results in enhanced cytokine production upon stimulation of myeloid and NK cells with nonrelated micro-organisms, as well as an increased phagocytosis and killing of pathogens [50,69] Induction of TI in myeloid cells seems also to have important adjuvant effects on lymphocyte activation, as a randomized trial of BCG as a booster for influenza vaccination has demonstrated improved lymphocyte responses [70]. These initial data provide arguments that TI may also improve antitumor lymphocyte responses and may be beneficial as adjuvant therapy in malignancies.…”
Section: Ti: Adaptation Within Innate Host Defensementioning
confidence: 99%